2011
DOI: 10.1074/jbc.m111.228833
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of the RNase H2A Subunit Mutations That Cause Aicardi-Goutières Syndrome

Abstract: Mutations in the three genes encoding the heterotrimeric RNase H2 complex cause Aicardi-Goutières Syndrome (AGS). Our mouse RNase H2 structure revealed that the catalytic RNase H2A subunit interfaces mostly with the RNase H2C subunit that is intricately interwoven with the RNase H2B subunit. We mapped the positions of AGS-causing RNase H2A mutations using the mouse RNase H2 structure and proposed that these mutations cause varied effects on catalytic potential. To determine the functional consequences of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…This phenomenon strongly suggested that the GRG motif mutations in RNase H2A affect the binding affinity tremendously, which in turn affected the enzyme's activity. This was consistent with a previous report by Perrino et al which demonstrated that G37S activity decreases with decreasing substrate binding affinity [10]. The mutation of the GRG motif may affect the dihedral angle of the loop and the surrounding residues.…”
Section: Substrate Binding Efficiency Of Rnase H2 and Its Mutantssupporting
confidence: 82%
See 4 more Smart Citations
“…This phenomenon strongly suggested that the GRG motif mutations in RNase H2A affect the binding affinity tremendously, which in turn affected the enzyme's activity. This was consistent with a previous report by Perrino et al which demonstrated that G37S activity decreases with decreasing substrate binding affinity [10]. The mutation of the GRG motif may affect the dihedral angle of the loop and the surrounding residues.…”
Section: Substrate Binding Efficiency Of Rnase H2 and Its Mutantssupporting
confidence: 82%
“…The K d values are shown in Table 2. The wild type RNase H2 complex bound to FAM-labeled duplex DNA with a K d value at 26.1 nM, which is comparable to that reported in literature [10]. K d values of the 4 mutants (G37A, G37S, R38A, and G39A) are 1009.5 ± 91.41 nM, 100.2 ± 8.09 nM, 554.5 ± 43.88 nM, and 765.6 ± 79.04 nM, respectively.…”
Section: Substrate Binding Efficiency Of Rnase H2 and Its Mutantssupporting
confidence: 74%
See 3 more Smart Citations